2021
DOI: 10.1021/acs.inorgchem.0c03385
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(III) Complexes Based on an 18-Membered Macrocycle Containing Acetamide Pendants. Structural Characterization and paraCEST Properties

Abstract: We report a detailed investigation of the coordination properties of macrocyclic lanthanide complexes containing a 3,6,10,13-tetraaza-1,8­(2,6)-dipyridinacyclotetradecaphane scaffold functionalized with four acetamide pendant arms. The X-ray structures of the complexes with the large Ln3+ ions (La and Sm) display 12- and 10-coordinated metal ions, where the coordination sphere is fulfilled by the six N atoms of the macrocycle, the four O atoms of the acetamide pendants, and a bidentate nitrate anion in the La3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“… 110 The TightSCF and Grid7 (for Y) options were applied to increase the convergence tolerances and integration accuracies of the calculations from the defaults. Chemical shifts were determined as δ = (σ ref – σ) considering the shielding constant calculated for [Y(H 2 O) 8 ] 3+ ·16H 2 O as in ref ( 41 ). The calculations were carried out in aqueous solution and solvent effects were considered using the SMD solvation model.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“… 110 The TightSCF and Grid7 (for Y) options were applied to increase the convergence tolerances and integration accuracies of the calculations from the defaults. Chemical shifts were determined as δ = (σ ref – σ) considering the shielding constant calculated for [Y(H 2 O) 8 ] 3+ ·16H 2 O as in ref ( 41 ). The calculations were carried out in aqueous solution and solvent effects were considered using the SMD solvation model.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…Thus, the most popular macrocycles in biomedicine are those arising from the modification of the platforms tacn, cyclen, and cyclam, mainly by the inclusion of acetate pendant arms . Nevertheless, inserting pyridine moieties into the macrocyclic backbone may be worth considering since their introduction tends to increase rigidity in the ligand and to cause alterations in its basicity, leading to significant modifications in the thermodynamic and kinetic properties of its complexes. Accordingly, hexaazamacrocycles derived from the condensation of 2,6-diformilpyridine and ethylenediamine such as those depicted in Chart , have proven to successfully host lanthanide ions, due to their spacious macrocyclic cavity and their capacity to satisfy the coordination requirements of these large ions through the functionalization of their four secondary amines. Furthermore, it has been found that binding constants for H 4 L 1 with large metal ions are considerably high (log K ∼ 22) and promising indications of kinetic inertness also exist for H 4 L 1 , L 3 , and L 5 lanthanide complexes. ,, …”
Section: Introductionmentioning
confidence: 99%
“…An estimate of the contact shifts was obtained by performing DFT calculations for the Gd­(III) analogues, which provide straightforward access to the values of A / ℏ . ,, The results of these calculations for [Dy­(CB-TE2PA)] + are presented in Table , while those obtained for [Dy­(PYTA)] − are presented in the Supporting Information (Table S1). Contact shifts were subsequently obtained from the A / ℏ values using eq and ⟨ S z ⟩ = 22.0 .…”
Section: Resultsmentioning
confidence: 99%
“…38–44 Although not yet reported for radiopharmaceutical uses, PYTAM (Scheme 1) is a decadentate macrocyclic chelator with four acetamide pendant arms, belonging to the PYAN family, first used for the complexation of lanthanides, resulting in very inert complexes. 45,46…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44] Although not yet reported for radiopharmaceutical uses, PYTAM (Scheme 1) is a decadentate macrocyclic chelator with four acetamide pendant arms, belonging to the PYAN family, first used for the complexation of lanthanides, resulting in very inert complexes. 45,46 Herein, we present a study on the coordination ability towards [ nat/203 Pb]Pb(II) of PYTAM and another three new decadentate hexaazamacrocylic chelators. Additional rigidity was introduced into the PYTAM framework by incorporating two cyclohexyl units, giving rise to the new chelator CHX-PYTAM.…”
Section: Introductionmentioning
confidence: 99%